1998
DOI: 10.1677/joe.0.1560485
|View full text |Cite
|
Sign up to set email alerts
|

Human placenta and fetal membranes contain peptide YY1-36 and peptide YY3-36

Abstract: Extracts of human term amniotic, placental, and chorion/ decidua tissue contained, respectively, 4·36 2·79 (pmol/g wet wt; mean ...; n=5), 2·78 0·5 (n=5) and 0·68 0·68 (n=5) peptide YY (PYY)-like immunoreactivity. Using a specific PYY antiserum, gel filtration chromatography and reverse-phase high performance liquid chromatography (HLPC), amniotic, placental and fetal intestinal tissue extracts were demonstrated to contain PYY-like immunoreactivity consisting of equal amounts of PYY 1-36 and PYY . The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
1
4
0
1
Order By: Relevance
“…We found that PYY (3-36) accounted for a high percentage (almost 50%) of total PYY immunoreactivity in our study population, similarly to previous reports in adults (1), and in accordance with the demonstration of both isoforms of PYY, in equal amounts, in fetal intestinal tissues (17). However, it contradicts the results of the study of Adrian et al showing that, on gel permeation chromatography, the majority of circulating PYY-like immunoreactivity, in the neonate, eluted in an identical position to the pure 36 amino acid PYY standard; thus represented the PYY (1-36) (18).…”
Section: Discussionsupporting
confidence: 93%
“…We found that PYY (3-36) accounted for a high percentage (almost 50%) of total PYY immunoreactivity in our study population, similarly to previous reports in adults (1), and in accordance with the demonstration of both isoforms of PYY, in equal amounts, in fetal intestinal tissues (17). However, it contradicts the results of the study of Adrian et al showing that, on gel permeation chromatography, the majority of circulating PYY-like immunoreactivity, in the neonate, eluted in an identical position to the pure 36 amino acid PYY standard; thus represented the PYY (1-36) (18).…”
Section: Discussionsupporting
confidence: 93%
“…Although the potential role of PYY- in fitting the reproductive function to body energy stores is still poorly characterized, recent data suggested its involvement in the control of reproductive axis. Thus, in addition to the reported presence of PYY-(3-36) in placenta (62), recent data from our laboratory indicated that PYY-(3-36) stimulates in vitro FSH and LH secretion by pituitaries from prepubertal female and male rats and inhibited in vitro GnRH secretion selectively in males (17). In addition, infusion of PYY- into the lateral ventricle rapidly inhibited estrous behavior in ovariectomized steroid-primed hamsters (35) and decreased LH secretion in prepubertal male rats (17).…”
mentioning
confidence: 64%
“…The expression of the peptide YY and insulin receptors (as well as the associated glucose transporter) expression has also been noted in endometrial cells with variation during the menstrual cycle, although the roles of these hormones in the endometrium requires further investigation (Xiao et al, 1998;Mioni et al, 2012).…”
Section: Gut and Adipose Hormones: Endometrial Development And Functionmentioning
confidence: 99%